Subgroups of relational job characteristics and their differences in turnover intention and subjective well-being among nurses: a latent profile analysis - Yi-ping Chen; Yifei Li; Jie Zhang; Juan Li; Xiu-fen Yang; Lile Xiong; Guili Xia; Jingping Zhang (BMC, 2024)
Abstract Objective Relational job characteristics include perceived social worth and perceived social influence. Good relational job characteristics mean that nurses have high prosocial behavior. The purpose of this study was to explore the potential profile of nurses' relational job characteristics, influencing factors and their differences in turnover intention and subjective well-being, thus finding the most suitable clinical relationship job characteristics. Methods A cross-sectional survey was conducted among 1013 clinical nurses using the general demographic data questionnaire, Relational Job Characteristics scale, Turnover Intention Questionnaire and Campbell index of well-being. A latent profile analysis was performed to explore relational job characteristics latent profiles. Multinomial logistic regression analysis was conducted to examine the predictors of profile membership, and a one-way analysis of variance was applied to compare the turnover intention and subjective well-being in each latent profile. Results Five latent profiles were identified and labeled 'High prosocial job characteristics' profile (20.7%), 'Moderate prosocial job characteristics' profile (41.7%), 'High social worth-low social impact perceived' profile (6.3%), 'Low social worth‐high social impact perceived' profile (18.8%) and 'Low prosocial job characteristics' profile (12.5%). Factors affecting the different types of nurse relationship job characteristics include age, marital status, hospital department, nursing years, professional title and hospital position. Among them, chief nurse, nurses with more than 20 years of nursing experience and obstetrics and gynecology nurses were more likely to be 'high prosocial job characteristics' profile. The turnover intention of nurses in 'high prosocial job characteristics' profile was significantly lower than that of other profiles, and their subjective well-being was significantly higher than that of other profiles. Conclusion Improving nurses' perception of social worth and social impact on clinical work can improve nurses' prosocial behavior and subjective well-being, and reduce their turnover intention. Nursing managers or policy makers can formulate targeted intervention measures according to the influencing factors of potential profiles.